P277 Measuring sedentary behaviours in patients with idiopathic pulmonary fibrosis using wrist-worn accelerometers. (15th November 2016) - Atkins, CP; Baxter, M; Jones, AP; Wilson, AM
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) patients suffer increasing functional limitation as the disease progresses. Increasing sedentary behaviour (SB) time has been associated with poorer health-related quality of life. Determining thresholds for activity vigour in patients with respiratory disease is difficult due to variability in cardiorespiratory limitations between individuals. SB time is not confounded by this limitation and may be a more reliable measurement of activity in patients with severe exercise limitation such as IPF. Methods: Thirty-nine IPF patients wore a GENEActiv actiwatch continually for 7 days. Participants underwent measurement of forced vital capacity (FVC), diffusion capacity of carbon monoxide (DLCO), 6 minute walk distance (6MWD) Results: Valid data was downloaded from 35 of the 39 participants (89.7%). Mean acceleration intensity recorded in the most active 5 hours of each day (M5; in milli-g) were 43.8 milli-g and time spent in SB was 551.7 minutes per day, higher than estimates of time in SB in similar age demographics in previous studies. Daily SB time correlated moderately with M5 values (pearson correlation −0.366, p = 0.030). Only M5 values predicted time in SB. No variability in SB time was seen by day of the week. There was a trend towards higher one and two year mortality with greater periods of time in SB. Conclusions: Wrist-worn accelerometers reliably collected data and were well tolerated. IPF patients spent long periods of time in sedentary behaviours. Of the standard clinical measures used, 6MWD predicted daily activity but not SB time; no clinical measures predicted SB time. Increased time in SB may be associated with poorer outcomes in IPF patients; replacing time in SB with light activity may be a more achievable goal than increasing moderate or vigorous activity levels in IPF patients and improve outcomes.